ANALYSIS OF THE INFLUENCE OF GOLD NANOPARTICLE ADDITION TO PHOTOLUMINESCENCE EMISSION INTENSITY AND DECAY TIME OF 618-CDSE QUANTUM DOTS - Muhammad Lawrence Pattersons; Isnaeni Isnaeni (Spektra: Jurnal Fisika dan Aplikasinya)
Abstrak